Impact of Civic Responsibility on Decision to Vote among Adults - Heeba Nashmena; Subha Malik; Madiha Nadeem (Journal of Research in Social Sciences, 2022)
Globally, the engagement of citizens in civic responsibility and politics is considered critical for the nurturance of democratic culture. In this context, this study was conducted to understand the citizens’ attitude toward civic responsibility and the decision to vote along with factors considered influential in determining this attitude. It was a mixed-method study. For a quantitative study, a survey was conducted by collecting data from 300 respondents: 150 from the rural background and 150 from the urban background. Quantitative results revealed that educated respondents belonging to the urban area and falling in the category of high monthly income are more likely to cast vote because according to them their vote can bring change, the vote is their responsibility and vote brings a real representative, whereas uneducated people belonging to the rural falling in the category of the low monthly income group are found more motivated for voting without casting vote. Additionally, the political identity of the candidate tends to influence the voting behavior of adults and it was also seen that age is an important demographic factor in determining the voting trend. Civic responsibility was found positively correlated with a) Reasoning which implies that voting is a responsibility and duty, b) Personal identity of the candidate, and c) Integrity which is the political experience of the candidate. Qualitative analysis of respondents living in urban and rural areas found that vote is a responsibility, people cast votes for the development of the country, and women's empowerment or equal right. However, respondents of both groups, rural and urban found to have a negative perception of politics and barriers to women’s voting. These findings can be used as an important source of information for policymakers to design special policies and initiatives to promote civic responsibility and the right of casting votes for the citizens.